Investigation of Acute Phase Proteins in Cattle Infected with Mycobacterium bovis - Çenesiz, S; Şahin, B; Akpinar, RK; Kiliçoğlu, Y (Journal of the Hellenic Veterinary Medical Society, 2023)
Tuberculosis (TB) is a contagious and zoonotic disease that adversely affects human and animal health, caused by the formation of tubercules in a caseous character in the lungs, other tissues and organs. The causative of the disease is Mycobacterium bovis. An increase or decrease in acute phase protein (APP) levels is observed in various bacterial, viral and parasitic diseases in cattle. Therefore, in this study, it was aimed to determine the changes in the levels of AFPs in cattle infected with M. bovis. In the study, 26 tuberculosis suspected and 10 healthy cattle blood serums collected from various enterprises in Samsun were used. Rose bengal plate test and complement fixation test were applied in serum by taking blood into heparin containing tubes from vena jugularis of cattle. Whole blood samples were subjected to gamma interferon ELISA test. Haptoglobin (Hp), serum amyloid A (SAA), albumin and total protein (TP) levels, which are among the acute phase proteins, were determined in the blood serums taken from the groups. As a result of the analysis, when the AFP levels of the cattle infected with M. bovis and the cattle in the healthy group were compared, it was determined that haptoglobin (p < 0.01), serum amyloid A (p < 0.01) and total protein (p < 0.01) levels, which are AFPs increased statistically significantly compared to the healthy group, while the albümin (p > 0.05) level decreased, but there was no statistically significant difference. Keywords: acute phase protein (APP); cattle; mycobacterium bovis; tuberculosis (TB),